Prosthetic Valve Candida Endocarditis: A Case Report with 18F-FDG-PET/CT as Part of the Diagnostic Workup - Soile Pauliina Salomäki; Antti Saraste; Päivi Jalava-Karvinen; Laura Pirilä; Ulla Hohenthal (Case Reports in Cardiology)
Diagnosis of Candida spp. infective endocarditis (IE) is challenging, and diagnostic delays are common. We describe two patients with Candida spp. prosthetic valve endocarditis (PVE) and 18fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG-PET/CT) as a part of diagnostic workup. We also refer to 5 other cases we found from the published literature. These cases highlight that 18F-FDG-PET/CT can improve diagnostic accuracy in prosthetic valve Candida endocarditis.